Fantastic frogs! - Robinson, Fay.; Cassels, Jean (New York : Scholastic, 1999)
Introduces the growth, food, habitats, colors, and shapes of different kinds of frogs.
"Cartwheel books."
Keywords: Frogs -- Juvenile literature; Frogs